Особливості перекладу англійською мовою власних назв (дійових осіб) у драмі-феєрії Лесі Українки «Лісова пісня» - Гандзюк, Олександра; Handyzuk, Oleksandra (Східноєвропейський національний університет імені Лесі Українки, 2014)
Розглянуто семантичні особливості перекладу назв дійових осіб у драматичному тексті. Проаналізовано прийоми відтворення міфологічних реалій як факторів створення своєрідного міфологічного колориту драми- феєрії Лесі Українки «Лісова пісня» в англійському перекладі. The article deal with semantical specification of the translation of the actors names in dramatic text. The nаmеs of the scientists involved in this problem are given in this article. The article considers specification of the translation of the actors in drama of Lesya Ukrainka «Forest song». The names of the general actors is analyzed. Translation of the names of the mythological persons in drama of Lesya Ukrainka «Forest song» are noted. Methods of transfer of mythological realities as elements of creating of original mythological color in drama of Lesya Ukrainka «Forest song». Some difference in the meaning the name of the actors in the Ukrainian language and in English one are explained in this article. Inexpediency some forms are analyzed. Conclusions about similarity this translation in English language to the European models are done.
Specificity of English Translation the Proper Names (Actors) in the Drama of Lesya Ukrainka «Forest Song»
Keywords: адекватність; переклад; українська мова; англійська мова; власні назви; translation; adequacy; Ukrainian; English; proper names